PHAGO PHARMACOLOGY ON THE GO. GAMIFICATION APPROACH IN CASE LEARNING PROCESS - Evelyn Ongkodjojo; F.V Lanny Hartanti; Bernadette Dian Novita; Sianty Dewi; Dyana Sarvasti; Diga Albrian Setiadi; Fransiskus Reynaldy; Ivan Priyantono; Shavna Arfi Rasyid; Felix Kurniawan Adithia; Iwan Satria Djuanda (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Learning process among medical students have developed along with technological advances so that it can be useful for users. One of the breakthroughs in the world of medical education is the development of serious games using multimedia technology that are relatively small in size so that they can be accessed using computers or devices named Pharmacology on the Go (PHAGO). The implementation stage was done by testing prototype game on 88 users October 20, 2021. Evaluation was done by using a feedback questionnaire for PHAGO users, shows 79 (89.8%) users who agree and strongly agree that the PHAGO application helps users understand the use of Pharmacology for clinical application. The results of the Wilcoxon test in evaluating the increase in students' knowledge with Pre Test and Post Test showed that there was a significant difference (p = 0.000). The existence of serious game stimulates an active learning process to create a learning environment that encourages the development of interpersonal, communication and problem solving skills. PHAGO is expected to be a forum that supports students to be able to independently study pharmacology in a fun and easy-to-understand way.